2020
DOI: 10.22541/au.160193327.77665145/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elastase and Exacerbation of Neutrophil Innate Immunity are Involved in Multi-Visceral Manifestations of COVID-19

Abstract: Background: Many arguments suggest that neutrophils could play a prominent role in COVID-19. However, the role of key components of neutrophil innate immunity in severe forms of COVID-19 has deserved insufficient attention. We aimed to evaluate the involvement of Neutrophil Elastase, histone-DNA, and DNases in systemic and multi-organ manifestations of COVID-19. Methods: We performed a multicenter study of markers of neutrophil innate immunity in 155 cases consecutively recruited in a screening center (ambulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
(97 reference statements)
1
2
0
Order By: Relevance
“…Also, our study findings displayed that NE levels in ICU patients were significantly elevated than in non-ICU patients. Our results were in line with a recent study conducted by Louis Guéant et al [30] who revealed that the NE levels were significantly elevated in COVID-19 patients. The recent evidence has represented the pathogenic role of NE in respiratory viral infections [36] and lung injury [27] , [37] , [38] .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Also, our study findings displayed that NE levels in ICU patients were significantly elevated than in non-ICU patients. Our results were in line with a recent study conducted by Louis Guéant et al [30] who revealed that the NE levels were significantly elevated in COVID-19 patients. The recent evidence has represented the pathogenic role of NE in respiratory viral infections [36] and lung injury [27] , [37] , [38] .…”
Section: Discussionsupporting
confidence: 94%
“…Further evidence has highlighted the crucial function of NE in pathologic conditions, including chronic obstructive pulmonary disease and lung injury [27] , [28] , [29] . Besides, recently, it has been noticed that NE may be implicated in the pathogenesis of COVID-19 [30] . Therefore, the present study evaluated the association between dynamic changes in NE levels associated with inflammatory markers (IL-6 and IL-8), anti-inflammatory markers (IL-4, IL-10), and vitamin D levels on the three-time points (T1-T3) in ICU and non-ICU COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…MPO has been indicated as a potential prognostic marker for the severity of COVID-19 (17). MPO has also been associated with lung epithelial and endothelial damage in cases of severe COVID-19 (23), potentially accelerating oxidative lung tissue injuries in patients infected with SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%